Avaliação dos tempos de espera nas etapas de fabricação de Aciclovir 400 mg comprimido (holding time studies) - Berdague, André de Oliveira (2021)
There are numerous challenges of the pharmaceutical industry to meet demand, and the lack of a well-designed holding time study can cause serious damage to industries and distributors. The study of holding time is directly related to the storage of pharmaceutical products, from the permanent or temporary storage of raw materials, semi-finished products and finished products until the moment of reaching the final consumer / patient, ensuring the quality of the product. Holding time studies are extremely important as they allow greater flexibility for the company and its production, ensuring the quality of intermediate and bulk pharmaceutical products, under the normal storage conditions, for a certain period. To prove that the waiting times of intermediate and bulk products, and their respective storage conditions, not impact the efficacy and safety of the drug, these batches should be submitted to the stability study. In this sense, this study demonstrated that the storage time between the productive stages does not interfere with the stability of the drug, proving that unforeseen events in the productive area that prevents the next processing step can be duly justified without the need for additional analysis, provided that the batch does not exceed the total accumulated storage time.